Synthesis of Some New Pyrazoline Derivatives and Related Compounds from Chalcones and their Antibacterial Activity - Naik, K.M.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Some new 1-H-3-(2'-hydroxy-5'-chloro-3'-nitrophen-1'-yl)-5- substituted phenyl-2-pyrazolines [2(a-j)] have been prepared by reaction of 2'-hydroxy-5'-chloro-3'-nitrochalcones [1(a-j)] with hydrazine hydrate in ethanol. Their acetyl and benzoyl derivatives [3(a-j), 4(a-j)] have been prepared by acetylation and benzoylation respectively.